Physical Activity and Quality of Life in People With Visual Impairments: A Systematic Review. (January 2022) - Caputo, Eduardo L.; Porcellis da Silva, Rafael B.; Leal da Cunha, Larissa; Krüger, Gabriele R.; Reichert, Felipe F.
Objective: This systematic review aimed to investigate the relationship between physical activity and quality of life (QOL) in people with visual impairments. Methods: Electronic searches were performed in PubMed, SPORTdiscus, CINAHL, Embase, and Web of Science. Observational studies describing the relationship between physical activity and QOL in adults with visual impairments were included. The Newcastle-Ottawa Scale (NOS) adapted for cross-sectional studies was used to assess the quality of the studies. Results: Overall, 327 studies were identified, and eight met the inclusion criteria. All studies had cross-sectional designs and seven were performed in developed countries. Physical activity was assessed objectively by one study, and five studies used the International Physical Activity Questionnaire. The World Health Organization Quality of Life Questionnaire was the most used instrument to measure QOL. Six studies reported a positive relationship between physical activity and QOL domains, as follows: life satisfaction, activity limitation, fair or poor health, physically and mentally unhealthy days, psychological health, and overall QOL. Conclusion: People with visual impairments who are engaged in physical activity are more likely to have better QOL outcomes.